Robust hydrophobic gold, glass and polypropylene surfaces obtained through a nanometric covalently bound organic layer. Issue 23 (3rd April 2020) - Mattiuzzi, Alice; Troian-Gautier, Ludovic; Mertens, Jérémy; Reniers, François; Bergamini, Jean-François; Lenne, Quentin; Lagrost, Corinne; Jabin, Ivan
Abstract : The grafting of a polyfluorinated calix[4]arene-tetradiazonium derivative on various surfaces led to the formation of very robust and stable hydrophobic monolayers. Abstract : The (electro)chemical grafting of a polyfluorinated calix[4]arene on gold, polypropylene and glass is reported. The modified surfaces were characterized by ellipsometry, atomic force microscopy (AFM), and by X-ray photoelectron spectroscopy (XPS). A nanometric, robust and uniform monolayer of covalently surface-bound calix[4]arenes was obtained on the three different materials. For all surfaces, contact angles higher than 110° were recorded, highlighting the hydrophobic character given by this ∼2 nm thin organic monolayer. Remarkably, the contact angle values remained unchanged after 18 months under a laboratory atmosphere. The results presented herein thus present an attractive and sustainable strategy for bringing hydrophobic properties to the interface of a wide range of materials.